Respon Cabai Rawit Varietas Hiyung (Capsicum frustescens L.) Terhadap Konsentrasi PGPR (Plant Growth Promoting Rhizobacteria) pada Ultisol di Kabupaten Tanah Laut - Bayuna Prama Arta; Gusti Muhammad Sugian Noor; Anna Maria Makalew (Universitas Lambung Mangkurat, 2019)
The purpose of this research is to know the effect of PGPR concentration from the combination of bamboo root isolate and mother root isolate to the growth and yield of chili hiyung plant and to know the difference of growth and yield of chili hiyung plant with some PGPR concentration treatment from the combination of bamboo root isolate and isolate the daughter's roots shy at different concentrations. This research is a single factor experiment with Complete Random Design (RAL) 6 (six) treatment design using polybag. The treatments used were P0 (control) without PGPR, P1 (PGPR 2.5 mL L-1 water), P2 (PGPR 5.0 ml L-1 water), P3 (PGPR 7.5 ml L-1 water) P4 (PGPR 10.0 ml L-1 water) and P5 (PGPR 12.5 ml L-1 water). The results showed that PGPR concentration from bamboo root isolate and mother shy root isolate did not affect all observed variables, because it was suspected as a result of pest and disease attack during cultivation.